Local participation in REDD+: lessons from the Eastern Brazilian Amazon - Cromberg, M.; Duchelle, Amy E.; Oliveira Rocha, I. de (MDPI, 2014)
There are concerns that local people will not be genuinely involved in initiatives to Reduce Emissions from Deforestation and Forest Degradation (REDD+). We analyzed local participation in the design of one REDD+ project in the eastern Brazilian Amazon, and assessed local hopes, worries and recommendations for the project through four community focus groups and interviews with 137 households at the site. Our results showed that only one-third of households interviewed (31%) had enough information about the project to describe it accurately. Of those, the majority (60%) hoped that the project would improve their incomes, followed by improving their agricultural production (33%) and helping protect forests (26%). While increasing household incomes was the dominant hope, people’s recommendations revealed that they favored non-monetary forms of compensation over the direct cash payments included in the proponents’ package of incentives. Their main recommendation was that the project should help improve their production systems through access to technical assistance, machinery and training, while valuing local production systems (46%). Our study highlights the need for participation that goes beyond passive consultation with local people to develop REDD+ interventions that best reflect local knowledge, land use practices and aspirations.